Late prematurity and adiposity in adolescents: Evidence from "Children of 1997" birth cohort. (18th September 2015) - Hui, L.L.; Lam, Hugh S.; Leung, Gabriel M.; Schooling, Catherine M.
Abstract : Objective: The association of late prematurity with later adiposity is unclear, and the mediating role of infant growth is seldom studied. We assessed the association of late prematurity with markers of adiposity in adolescence and tested whether accelerated infant weight gain mediated the association. Methods: In the Chinese birth cohort "Children of 1997, " we used multivariable linear regression to assess the adjusted association of late premature ( n = 295), compared to term ( n = 6874), births with markers of adiposity at 14 years. We tested whether any association was mediated by accelerated weight gain from birth to 12 months, i.e., a change in weight z‐score ≥0.67. Results: Late premature births had greater body mass index (BMI) z‐score (0.21, 95% confidence interval (CI) 0.07, 0.35), waist–hip ratio z‐score (0.16, 95% CI 0.03, 0.29), and waist–height ratio z‐score (0.27, 95% CI 0.14, 0.40) than term births in adolescence. The association of late prematurity with higher adolescent BMI, but not waist ratios, was mediated by accelerated infant weight gain. Conclusions: Late prematurity was associated with higher BMI and waist ratios in adolescence, but only the association with BMI was mediated by infant weight gain, suggesting vulnerability to metabolic risk in late premature births may arise through multiple pathways.